2019
DOI: 10.1038/s41438-018-0077-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci and candidate genes for primary metabolite content in strawberry fruit

Abstract: Improvement of nutritional and organoleptic quality of fruits is a key goal in current strawberry breeding programs. The ratio of sugars to acids is a determinant factor contributing to fruit liking, although different sugars and acids contribute in varying degrees to this complex trait. A segregating F1 population of 95 individuals, previously characterized for several fruit quality characters, was used to map during 2 years quantitative trait loci (QTL) for 50 primary metabolites, l-ascorbic acid (L-AA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…FaDHAR and FaGMP collocated with the QTL detected only 1 year on LG VII-1. Recently, a transcriptomic analysis by RNA-seq in pools of progeny lines contrasting in ascorbate content derived from the same population identified differential expression of gene MANNOSE-6-PHOSPHATE ISOMERASE 1 ( FaM6PI1 ) while FaMIOX was not differentially expressed (Vallarino et al, 2019). The FaM6PI1 gene was also located within the confidence interval of the major QTL detected on LG V-I, and it is highly similar to the Arabidopsis PMI gene that encodes the first enzyme in the SW pathway (Maruta et al, 2008).…”
Section: Approaches To Increase Ascorbate In Fruitsmentioning
confidence: 99%
“…FaDHAR and FaGMP collocated with the QTL detected only 1 year on LG VII-1. Recently, a transcriptomic analysis by RNA-seq in pools of progeny lines contrasting in ascorbate content derived from the same population identified differential expression of gene MANNOSE-6-PHOSPHATE ISOMERASE 1 ( FaM6PI1 ) while FaMIOX was not differentially expressed (Vallarino et al, 2019). The FaM6PI1 gene was also located within the confidence interval of the major QTL detected on LG V-I, and it is highly similar to the Arabidopsis PMI gene that encodes the first enzyme in the SW pathway (Maruta et al, 2008).…”
Section: Approaches To Increase Ascorbate In Fruitsmentioning
confidence: 99%
“…In order to breed for higher concentrations of healthrelated phytochemicals such as polyphenols in the cultivated strawberry, it is first essential to understand the inheritance of such compounds. Many quantitative trait loci (QTL) mapping studies have been undertaken to investigate various aspects of cultivated strawberry fruit quality, including the identification of QTL for total anthocyanin content 18 , overall sweetness, titratable acidity and ascorbic acid content 19 , and fruit primary metabolite content 20 . More recently, a study of a 'Delmarvel' × 'Selva' progeny identified many QTL similar to previous studies 21 , and QTL for fruit quality have been identified in 23 related F 1 progenies using a pedigree-based approach 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation and genetic mapping of both specialized (polyphenolics, flavor components) and primary (sugars, organic acids) metabolites are indispensable to identify the genetic architecture of fruit sensorial and nutritional quality in cultivated strawberry. (20,4547). In addition, genetic studies allow pinpointing genotypes that can be used in a breeding scheme for the genetic improvement of strawberry.…”
Section: Discussionmentioning
confidence: 99%
“…(10), which are typically bi-parental populations in cultivated strawberry. (20,4547). Using such a bi-parental population issued from a cross between two parents with contrasted sensory trait values (20) and by additionally breaking down the flavonoid composition to its individual chemical components (22), we were able to map mQTLs for each chemical compound from the three flavonoid chemical classes detected in strawberry fruit.…”
Section: Discussionmentioning
confidence: 99%